The Gokteik Viaduct: A Tale of Gentlemanly Capitalists, Unseen People, and a Bridge to Nowhere - David C. Wohlers; Tony Waters (Social Sciences, 2022)
This article explores technical and socio-political factors that impacted construction of the Gokteik Viaduct railway bridge in Shan State, Burma, and the recurring failure of political powers to complete a continuous railway between Rangoon (Yangon) and Yunnan. Under rather contentious circumstances, the British government awarded an American steel company with the contract to construct what would become the world’s longest railway trestle bridge at the time of its completion in 1900. As an engineering marvel of its era, the Gokteik Viaduct is in the same category as the Eiffel Tower in Paris. Until now, however, scarce research has explored the Gokteik Viaduct in terms of historicity and factors that ultimately prevented this structure from fulfilling its intended purpose of transporting trainloads of marketable goods between Burma and Yunnan. This raises an ironic question: How could engineers construct such a remarkable bridge to service a railway that was never finished? Furthermore, why does the Gokteik Viaduct largely remain unexamined in terms of its noteworthy place in the geopolitics of Southeast Asia? In answering such questions, the authors conclude that the “unseen” story of the Gokteik Viaduct is not only about engineering prowess but of a political and social environment that continues to bedevil massive infrastructure projects in Upper Burma today.